MASKER GEL DARI EKSTRAK DAUN JAMBU BIJI MERAH (Psidium guajava L.) - Densi Selpia Sopianti; Abdul Aziz Zulhakim; Tri Yanuarto (Jurnal Komunitas Farmasi Nasional, 2022)
Antioxidant compounds can reduce the adverse effects on the skin due to the presence of free radicals. One of the plants that contain antioxidants is guava red leaves (Psidium guajava L) which in the past, the Bengkulu community, especially young women, often used guava leaves as a face mask that was pounded and rubbed on the face. There are developments in the times that demand everything in a more practical form so that the aim of the study was to find out whther the formulation of a gel mask from guajava leaf met the physical requirements for a gel mask. The method in this study uses an experimental method, which begins with the extraction of red guajava leaf using the maceration method with 96% ethanol solvent. Gel masks were made with various concentrations of guava leaf extract F0 0%, F1 3%, F2 6% and F3 9%. Further evaluation of the preparations included Organoleptic Test, Homogeneity Test, pH Test, Spreadability Test, Viscosity Test, Irritation Test, Adhesion Test, Dry Time Test and Hedonic Test. The evaluation results show that the four formulas have met the required evaluation requirements.